The Strategy of the Environmental Agency in the Management of Green Open Spaces in Bantul Regency - Nafrah Maudina; Dewi Sekar Kencono (Department of Public Administration, Universitas Negeri Surabaya, 2022)
The purpose of this study is to explain the strategy of the Environmental agency of Bantul Regency in responding to the lack of green open space. The existence of green open spaces (RTH) is an important element in forming a comfortable and healthy urban environment. Green Open Spaces in Bantul District, especially City Parks, still need more attention. Green open space in Bantul Regency is still at 13.65% and far below the minimum standard of urban green space, which is 30%. This study uses a qualitative method. The data source is the Environmental Agency of Bantul Regency and related parties. Data collection techniques with interviews, observation, and document study. The results of this study indicate several strategies carried out by the agency for green open spaces. The strategy undertaken is to increase community and private involvement through dissemination, involve the community in providing facilities and infrastructure, and make rules and sanctions related to violations or breaking into green open spaces. In addition, this strategy is implemented using an ecological and economic sustainability approach so that green open space also has a socio-cultural impact on the community.